Study guides

Q: If 4p plus 3 equals -6p plus -5 what is p's value?

Write your answer...

Submit

Related questions

You can combine like terms of p to get 6p. If you are given what p equals you can solve for the completely numerical answer.

-9p + 6p = -3p

p=1125

answer is p/5. problem: {[(p^2)-3p]/[(p^2)-6p+9]}/{20/(4p-12)}

p = 4

14 + 6p = 6 + 7p 8 = p

If: 6p+3 = 8p+6 Then: p = -3/2 or -1.5

The idea is to subtract 10p minus 4p.

Unfortunately, limitations of the browser used by Answers.com means that we cannot see most symbols. It is therefore impossible to give a proper answer to your question. Please resubmit your question spelling out the symbols as "plus", "minus", "equals". My guess - and it is a guess, is 6*(p + 2) - 2p = 6p + 12 - 2p = 4p + 12 where the + is missing throughout. But it could be 6*(p - 2) - 2p = 6p - 12 - 2p = 4p - 12 where most of the - are missing.

Factor x2 plus 12xp plus 36p2 is (x+6p)(x+6p).

17 + 6p = 9 6p = -8 p = -8/6 p = -4/3

8p+4=6p+10 8p-6p=2p 10+4=14 2p=14 p=7

algebra8p +4 = 10 +6p+8p - 6p = +10 - 42p = 6p = 3

6p + 11 = 35 Therefore, 6p = 35 - 11 = 24 p = 24/6 p = 4

7P + 9 = 16 + 6P subtract 6P from BOTH sides P + 9 = 16 subtract 9 from both sides P = 7

3p + 6p = (3 + 6)p = 9p

We can not provide a numerical answer for this question as these (p and x) are variables and their value is not fixed (it varies). We have not been told the value of either variable. However we can simplify this expression.-2p + 4x - 6p = 4x - 8p.We have simply combined the -2p and the -6p, which we can do as 2 of something plus 6 of the same thing will always equal 8 of that thing.-2 + -6 = -8. Therefore -2p + -6p equals -8p and hence the answer above.

If: -17 = 6p-5 Then: p = -2

6p + 12q + 18r = 6 (p + 2q + 3r)

17p+17q+p-7q-6p = 12p+17q

Add like terms: 13 - 17 + 2p^2 - 19p - 6p^2 = -4 - 4p^2 - 19p

3p

This might be the stable isotope of beryllium, 9Be: alpha + 9Be -> 12C + n alpha: 2p + 2n Be: 4p + 5n left side: 6p + 7n C: 6p + 6n right side: 6p + 7n Incidentally, this would not be a decay, rather an transfer reaction, I think.

Assuming you mean 7 multiplied by just 2p and assuming that p is a variable then p is calculated by: (7 * 2p) + 3 - 8 = 6p + 29 14p - 5 = 6p + 29 14p - 6p = 29 + 5 8p = 34 p = 4.25

If: 6p-2-3p = 16 Then: p = 6

People also asked